2018
DOI: 10.1002/gcc.22528
|View full text |Cite
|
Sign up to set email alerts
|

Truncating mutations of TP53AIP1 gene predispose to cutaneous melanoma

Abstract: Genetic predisposition to cutaneous malignant melanoma (CMM) involves highly penetrant predisposing genes and low and intermediate penetrant predisposing alleles. However, the missing heritability in (CMM) is still high. For such and in order to identify new genetic factors for CMM, we conducted an exome sequencing study in high-risk CMM patients. Two rounds of exome sequencing were successively performed in 33 and 27 high-risk patients. We focused on genes carrying rare nonsense, frameshift, and splice varian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…It functions as an oncogene in pancreatic ductal adenocarcinoma (PDAC), retinoblastoma, and nasopharyngeal carcinoma ( Yuan et al, 2017 ; Zhang et al, 2019b ; Shao et al, 2020 ; Tang et al, 2020 ; Cheng et al, 2021a ; Gao et al, 2021 ; Lu et al, 2021 ; Wang et al, 2021 ). In some other cancers, such as non-small cell lung cancer, hepatocellular carcinoma, gastrointestinal cancer, and cutaneous melanoma, TP53TG1 serves as a cancer suppressor ( Benfodda et al, 2018 ; Xiao et al, 2018 ; Chen et al, 2021 ; Masoumi et al, 2021 ). Through TCGA analysis, expression of TP53TG1 is positively or negatively correlated with overall survival time in different cancers ( Zhang et al, 2019b ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It functions as an oncogene in pancreatic ductal adenocarcinoma (PDAC), retinoblastoma, and nasopharyngeal carcinoma ( Yuan et al, 2017 ; Zhang et al, 2019b ; Shao et al, 2020 ; Tang et al, 2020 ; Cheng et al, 2021a ; Gao et al, 2021 ; Lu et al, 2021 ; Wang et al, 2021 ). In some other cancers, such as non-small cell lung cancer, hepatocellular carcinoma, gastrointestinal cancer, and cutaneous melanoma, TP53TG1 serves as a cancer suppressor ( Benfodda et al, 2018 ; Xiao et al, 2018 ; Chen et al, 2021 ; Masoumi et al, 2021 ). Through TCGA analysis, expression of TP53TG1 is positively or negatively correlated with overall survival time in different cancers ( Zhang et al, 2019b ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that the high expression of TP53TG1 inhibited cancer cell apoptosis in PDAC and breast cancer ( Zhang et al, 2019b ; Shao et al, 2020 ) and promoted cancer cell apoptosis in non-small cell lung cancer, hepatocellular carcinoma, gastrointestinal cancer, and cutaneous melanoma ( Benfodda et al, 2018 ; Xiao et al, 2018 ; Chen et al, 2021 ; Masoumi et al, 2021 ). In this study, we constructed a TP53TG1-OE model in HeLa cell line to explore its role in cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…We calculated the riskScore using the following formula: riskScore = (0.153 × expr_ACSL1) + (0.022 × expr_ ALDH2) + (0.029 × expr_MTHFD2) + (0.265 × expr_MRPL13) + (− 0.417 × expr_TP53AIP1) + (− 0.086 × expr_ SLC1A1) + (− 0.137 × expr_ME3) + (− 0.302 × expr_BCL2A1). (The detailed descriptions of these 8 MRGs [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] are provided in Table 2).…”
Section: Construction Of the Risk Gene Signature By Lassomentioning
confidence: 99%
“…Inhibited TP53AIP1 expression impairs the ability to induce apoptosis in cancer cells. Low TP53AIP1 expression in various cancers promotes cancer progression 296,297 …”
Section: Regulatory Mechanisms Of P53 On Downstream Genesmentioning
confidence: 99%
“…Low TP53AIP1 expression in various cancers promotes cancer progression. 296,297 Apoptosis-inducing factor mitochondria-associated 2 (AIFM2) has significant homology to apoptosisinducing factor (AIF) and NADH oxidoreductase but lacks a mitochondrial localization sequence. AIFM2 is transcriptionally activated by p53, binds to DNA in a nonsequence-specific manner, and induces caspaseindependent apoptosis.…”
Section: P53 Induces Apoptosismentioning
confidence: 99%